Irisin in Adolescent Type 1 Diabetic Patients and its Relation to Diabetes Control and Atherosclerosis - El Dayem, Soha M.; Battah, Ahmed A.; El Bohy, Abo El Magd; Yousef, Rasha Nazih; Mohamed, Mai Magdy Abd El Wahed (Open Access Macedonian Journal of Medical Sciences, 2020)
AIM: The objective of this was to determine the role of irisin in adolescent type 1 diabetes (T1D) patients. METHODS: This study was conducted on 65 patients with T1D and 50 healthy individuals as control group. Serum irisin, glycosylated hemoglobin (HbA1c), lipid profile, oxidized low-density lipoprotein (OxLDL), urinary albumin/creatinine ratio; carotid intimal medial thickness (cIMT), and aortic intimal medial thickness (aIMT) were evaluated for all participant. RESULTS: HbA1c, lipid profile, albumin/creatinine ratio, OxLDL, irisin, aIMT and cIMT were significantly higher in diabetic patients. Irisin had a positive correlation with age of diabetic patients, onset of diabetes, mid arm circumference, waist/height ratio, body mass index, HbA1c, and cIMT. CONCLUSION: Irisin is a marker for detection of diabetes control and early detection of subclinical atherosclerosis. Irisin had a relation with obesity.